Biomechanical Study of Smash Movement Technique in Volleyball: On the Initial Step Movement of Smash in Sports Education Students of UMKT - Situmorang, Vista Tama; Raharja, Andri Tria (FKIP - Universitas Riau, 2025)
This study aims to analyze the biomechanical aspects of the initial steps in the smash technique in volleyball, focusing on the distance of the steps taken by the player before the take-off phase. The smash technique is one of the main movements in volleyball that requires strength, speed, and good body coordination, including in the initial stages. This study uses a quantitative descriptive approach with an observation method through video recording of two Physical Education students who perform the smash movement. The data were analyzed using Kinovea 2023.1.2 software to measure the distance of the steps from each initial phase to the vertical push-off. The results of the analysis show that the more the number of initial steps taken, the distance of the last step tends to decrease. The shortening of the distance of the last step can be interpreted as a biomechanical strategy of the body to create stability and optimal position before pushing off. This finding is different from several previous studies which stated that the last step tends to be longer due to inertial thrust. Thus, the results of this study provide a new perspective in the study of sports biomechanics, especially in the aspect of footwork towards the smash movement. This study is expected to be the basis for developing a more efficient smash technique analysis training pattern based on purposeful movement.